'Do you know where your cyanide kit is?': a study of perceived and actual antidote availability to emergency departments in the South West of England. Issue 1 (2nd March 2012) - Mitchell, Louisa J; Higginson, Ian; Smith, Jason E; Swains, Liam; Farrant, Jennifer; Gagg, James; Lindenbaum, Charlotte; Mathieu, Nick
Abstract : Objective: The authors set out to investigate perceived and actual availability of antidotes recommended for stocking in emergency departments (EDs) by the College of Emergency Medicine in EDs in the South West of England. Methods: Data collectors were asked to physically locate each relevant antidote in the ED, and check whether the recommended quantity was available. If the antidote was not available in the department, the data collector located where in the hospital stocks were available. Senior medical and nursing staff were asked to specify where they believed the antidotes were stored or who they would ask if they did not know. It was then ascertained whether their source of advice would have known the location. Results: 5 out of 6 departments returned data with an overall response rate from senior medical and nursing staff of 80%. Knowledge of common antidote locations was variable, and stocking of antidotes did not universally meet the College of Emergency Medicine recommendations. Conclusion: Stocking of important antidotes should be rationalised and simplified using central locations, preferably close to the ED. Clinically important antidotes may not be available for patients when they need them. Clear guidance should be available for staff detailing the location of antidotes. There is a need for clarification around the treatment of cyanide poisoning to facilitate rational antidote stocking for this potentially lethal condition.